Early zoeal development of the shrimp Hippolyte leptocerus (Decapoda, Caridea, Hippolytidae) GUILLERMO GUERAO (Spain), ESTEBAN HERNÁNDEZ (Spain) & ÁNGEL URZÚA (Germany) - Guerao, Guillermo; Hernández, Esteban; Urzúa, Ángel (Zootaxa, 2011)
The morphology of the first three zoeal stages of Hippolyte leptocerus (Heller, 1863) are described and illustrated in detail from laboratory-hatched material. The ovigerous females were collected on the Alfacs Bay, Ebro Delta, Spain (Western Mediterranean). The early larval stages (ZI, ZII, ZIII) showed the anterolateral margin of carapace with denticulations, a median tubercle behind rostrum, scaphocerite segmented distally (only ZI and ZII), exopodal seta at the maxillule and pleonite 5 with a pair of dorsolateral spines. The morphology of the first three zoeal stages of H. leptocerus is typical of species with an extended larval development. Morphological characteristics of the genus Hippolyte are discussed.